2020
DOI: 10.3389/fmed.2020.533675
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Postural Movements With Virtual Reality Technology in Healthy Young and Older Adults: A Cross-Sectional Validation Study for Early Dementia Screening

Abstract: With the ultimate aim of early diagnosis of dementia, a new body balance assessment system with integrated head-mounted display-based virtual reality (VR) has been developed. We hypothesized that people would sway more in anterior-posterior (AP) direction when they were exposed to a VR environment where we intentionally provoked movements in forward and backward directions. A total of 14 healthy older adults (OA) (73.14±4.26 years) and 15 healthy young adults (YA) (24.93±1.49 years) were assessed for group dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Recently VR exergames for adults that monitor and train physical activity have been developed for: posture ( Solis-Escalante et al, 2019 ; Carr et al, 2020 ; Imaoka et al, 2020 ), falls ( Chen et al, 2020 ; Liston et al, 2021 ), dual-task walking ( Kizony et al, 2017 ; Janouch et al, 2018 ; Kafri et al, 2021 ). As well as assessing cognitive health and providing comfort in patients with neurological diseases and communication difficulties (e.g., Stasolla et al, 2021 ).…”
Section: Exergames For Adults That Assess Physical Activity and Cogni...mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently VR exergames for adults that monitor and train physical activity have been developed for: posture ( Solis-Escalante et al, 2019 ; Carr et al, 2020 ; Imaoka et al, 2020 ), falls ( Chen et al, 2020 ; Liston et al, 2021 ), dual-task walking ( Kizony et al, 2017 ; Janouch et al, 2018 ; Kafri et al, 2021 ). As well as assessing cognitive health and providing comfort in patients with neurological diseases and communication difficulties (e.g., Stasolla et al, 2021 ).…”
Section: Exergames For Adults That Assess Physical Activity and Cogni...mentioning
confidence: 99%
“…As well as assessing cognitive health and providing comfort in patients with neurological diseases and communication difficulties (e.g., Stasolla et al, 2021 ). In addition, various exergames investigate the correlation of multisensory stimulation and age on realistic daily-life activities ( Wechsler et al, 2018 ; Souza-Silva et al, 2019 ; Carr et al, 2020 ; Imaoka et al, 2020 ). Some also investigate the maintenance of posture and the response to fall and how they are age-dependently influenced by sound and vision (e.g., Stapleton et al, 2014 ; Lupo and Barnett-Cowan, 2018 ).…”
Section: Exergames For Adults That Assess Physical Activity and Cogni...mentioning
confidence: 99%
See 2 more Smart Citations
“…A study analyzing postural sway behaviors of people with AD also found that attentional demand during dual-task activity and visual challenge contributed to the postural instability of the AD population (Bahureksa et al, 2017 ; Mesbah et al, 2017 ). With the aim of improving body balance assessment for dementia screening using a visual challenge, we have created a new assessment system combining a stabilometer and head-mounted display (HMD)-based virtual reality (VR) technology (Imaoka et al, 2020a ). The new system was developed to trigger postural sway in anterior-posterior direction intentionally by giving a visual flow of moving VR environments forwards and backwards.…”
Section: Introductionmentioning
confidence: 99%